Analysing Obesity Epidemicity and Endemicity: Introducing New Quantitative Indices - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
As obesity becomes more and more common, it will get (ormay already have) converted from an epidemic to anendemic. This opinion piece discusses theseepidemiological definitions in the context of obesity andproposes three obesity epidemicity indices to quantifytheir indices. It discusses the rationale behind using suchratios to measure endemicity. The discussion notes how thedifferent ratios give markedly divergent results and call forgreater attention to this aspect of obesity epidemiology. Keywords: Endemic, epidemic, epidemiology, noncommunicabledisease, overweight, obesity